A precarização das relações de trabalho no setor sucronergético no município de Ituiutaba (MG) - Araújo, Noeme Santos de (2019)
This Master's Dissertation aims to understand the precariousness of labor relations in the sugar-energy sector in the municipality of Ituiutaba (MG). To achieve this purpose, methodological procedures were used: interviews with workers in the Ituiutaba sugar-energy sector and the president of the rural workers of Ituiutaba; bibliographic research; and secondary data search with IBGE, UDOP, SIAMIG and UNICA. The results achieved highlight the territorialisation and expansion of sugarcane cultivation in Brazil, Minas Gerais and in the municipality of Ituiutaba, based on the encouragement of public policies and the insertion of national and international capital. The universe of work has undergone significant transformations over the years, but we have identified that there is currently a combination of new and old practices in the exploitation of labor relations, which could be verified through the precariousness of these relations in the sugarcane sector with regard to intensification the working day combined with the inspection by technological devices, the imposition of goals for productivity and the overexploitation of labor relations that increase the exposure to the risks of accidents at work and lead to sickness of the workers. It was possible to identify a total of twenty-two work accidents related to the cut of hands and fingers occurred during the exchange of the basal cutting knives of the harvesters, infarcts, fall of machine workers, besides accidents with thornbugs and venomous animals. The interviews with the workers point to an intense degradation of the work with strong consequences for health, with twenty-eight workers suffering some kind of illness after starting their work activities in the sugarcane sector of Ituiutaba (MG). The understanding of all these aspects indicates that legislative actions must be carried out that aim at changes and promote improvements in the process and labor relations.